In-situ growth of CoP wrapped by carbon nanoarray-like architecture onto nitrogen-doped Ti3C2 Pt-based catalyst for efficient methanol oxidation. (December 2022) - Zhan, W.; Ma, L.; Gan, M.
Abstract: Herein, we report an efficient bottom-up approach to construct the carbon encapsulated CoP nanoarray-like architectures onto the nitrogen-doped Ti3 C2 MXene Pt-based catalyst (Pt–CoP@CNT NA/N–Ti3 C2 ) by employing metal-organic frameworks (MOFs) as the sacrificial template. Benefiting from the catalytic effect for metals into MOFs and synergistic effect of Ti3 C2 substrate, homogenous nanotubes nanoarray-like structure is obtained on Ti3 C2 nanosheet. The unique heteroatom-doped 3D connected structure endows the catalyst with distinct structural merits, such as the carbon and nitrogen-enriched structures, large specific surface areas and excellent conductivity, leading to the high dispersion of ultrafine metallic Pt and efficient electronic/mass transfer, contributing to more exposed active sites of Pt surface. The fabricated CoP and doped nitrogen especially for those lattice nitrogen derived from the pristine MOFs can present exceptional co-catalytic effect, resulting in obtaining strong anti-CO poisoning capacity for catalyst. Therefore, the ultrahigh catalytic activity of per Pt active site for methanol oxidation reaction can be preserved. Besides, owing to the strong stability of carrier, the catalyst delivers a reliable long-term stability during the test. This work gives new ideal for the design of novel cost-effective 3D Ti3 C2 -based nanomaterial catalyst with excellent catalytic activity for methanol oxidation. Graphical abstract: Image 1 Highlights: The mesoporous carbon encapsulated CoP nanoarray-like architectures supported by nitrogen-Ti3 C2 is fabricated. Lattice nitrogen into Ti3 C2 delivers remarkable structural merits. High dispersion of ultrafine Pt nanoparticles and its strong anti-CO poisoning capacity result in sustained ultrahigh catalytic activity for per Pt active site. Excellent catalytic performance for methanol oxidation reaction in acid medium.